HEALTH AND SAFETY CHALLENGES IN THE TEXTILE INDUSTRY: A COMPREHENSIVE REVIEW - Vats, Nidhi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The study aimed to analyze the work environment and facilities provided by textile industries concerning health, safety, and other essential human needs. In today’s business landscape, corporate social responsibility (CSR) has become a crucial strategy, attracting the attention of researchers, academicians, and corporate leaders. Employees increasingly expect companies to operate ethically and uphold social responsibility in their business practices. This has led to the emergence of the CSR concept, emphasizing that businesses must address social, environmental, and economic responsibilities while ensuring ethical treatment of employees in their operations.[1] The assessment of workplace conditions in textile and chemical industries was conducted through a combination of qualitative and quantitative measures to evaluate employee satisfaction levels. The study found that workers in these industries are exposed to hazardous chemicals, toxic effluents, and poisonous gas emissions, often without adequate safety equipment. The results revealed that working conditions were generally unsatisfactory, posing significant health and safety risks that hinder productivity.[2,3] Additionally, many industries lack fundamental workplace facilities, with environmental factors such as temperature, humidity, noise, and lighting frequently failing to meet the National Environmental Quality Standards (NEQS). Inadequate physical conditions further exacerbate workplace hazards, increasing the risk of accidents and occupational illnesses. Employers and trade unions primarily focus on key concerns such as workplace safety, wages, and job security. The study highlights that maintaining a healthy work environment enhances productivity and employee morale while reducing workplace accidents, premature deaths, and healthcare costs. Implementing effective safety measures and improving working conditions in the textile industry is essential for ensuring worker well-being and long-term sustainability.